Analisis Risiko Operasional Guna Meminimalkan Produk Cacat Menggunakan Metode FMEA pada UMKM Konveksi Ragel Mandiri - Ikhsanur Rahmad; Febrina Agusti; Brillian Nur Diansari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to identify potential operational failures and prioritize corrective actions to minimize defective products at Konveksi Ragel Mandiri, a home-based school uniform garment industry in Sragen. The manufacturing process heavily relies on traditional manual labor, leading to a defect rate of 6.73%, which exceeds the company's 3% tolerance threshold. This descriptive analytical study utilizes a quantitative approach integrating Failure Mode and Effect Analysis (FMEA), Pareto Diagram, Fishbone Diagram, and the 5W+1H framework. Data were collected through field observations and expert interviews. The results identified 12 failure modes across the production stages. Based on the Risk Priority Number (RPN) evaluation, four critical failures exceeded the average threshold of 136.58: untidy sewing (RPN = 240), stitch skipping (RPN = 196), crooked sewing (RPN = 192), and inaccurate cutting (RPN = 168). Corrective recommendations developed through 5W+1H focus on technical and ergonomic improvements, including structured operator training, clear standard operating procedures (SOP), regular machine calibration, and specialized workspace leveling to effectively control high-risk operations.